CLIMATIC-INTENSIVE TESTS AVIATION CONSTRUCTION COMPOSITE MATERIALS - Горобець, П. І.; Хоменко, А. В. (Proceedings of National Aviation University (archive), 2020)
The reasons of reduction of durability and rigidity in designs from polymer composite materials under the influence of environmental factors are considered. The basic methods of climatic-strength tests of constructions from polymer composite materials are given, their main advantages and disadvantages are noted